Lithium manganese iron phosphate battery and shell forming method thereof
By using a dual-response system to detect manganese ion diffusion and stress distortion during the molding of lithium manganese iron phosphate battery housing, the problem of difficulty in timely discovering microscopic corrosion hazards in the existing technology is solved, and early detection and grading analysis of manganese ion-induced stress corrosion is realized, and the safety of the battery housing is improved.
Patent Information
- Application Number
- CN202510286460.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The prior art is difficult to promptly detect and evaluate the microcorrosion hazards caused by manganese ion activation during the molding of lithium manganese iron phosphate battery housing, which may cause serious safety accidents.
By adding a dual-response system in the liquid or semi-curing stage of the metal matrix, including organic coordination groups and mechanically sensitive particles with manganese ion coordination function, cyclic heat load and mechanical load are applied, and electrolytes containing phosphate are introduced to obtain the diffusion parameters and stress distortion parameters of manganese ions, and decoupling analysis is performed to obtain the stress corrosion data induced by manganese ions.
Early detection and grading analysis of manganese ion-induced stress corrosion is realized, the ability to capture microscopic hidden defects is improved, the probability of large-area diffusion or local concentration of stress corrosion is reduced, and the safety of the battery shell is ensured.
Smart Images

Figure CN119812600A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of detection technology in the production and manufacturing of battery shells, and in particular to a lithium manganese iron phosphate battery and a shell molding method thereof. Background Art
[0002] Lithium iron manganese phosphate (LiFeMnPO4) battery is a new type of lithium-ion battery. Its positive electrode material is lithium iron manganese phosphate, which has the advantages of good safety, long cycle life and low cost. This type of battery has broad application prospects in electric vehicles, energy storage systems and other fields.
[0003] During the manufacturing and service of lithium manganese iron phosphate batteries, the battery shell materials face special corrosion challenges. This is mainly due to the unique activation characteristics of manganese under specific temperature, humidity and electrochemical conditions, which makes the shell prone to microscopic side reactions during high-temperature welding, vacuum drying, liquid injection and other stages in the manufacturing process. This reaction can cause imperceptible early corrosion risks on the surface or inner layer of the shell. Unlike conventional metal materials, the shell of lithium manganese iron phosphate batteries is simultaneously subjected to high-temperature stress and mechanical deformation, as well as the migration and precipitation of manganese ions in a complex electrolyte environment. This "electrochemical-mechanical" coupling effect may form an enrichment of manganese corrosion products at local interfaces or gaps, leading to extremely small grain boundary cracks or local passivation layer peeling.
[0004] Traditional appearance inspection, hardness test or simple mechanical fatigue analysis is difficult to capture such hidden defects in the early stage. Once these potential corrosion points are aggravated during the later high-rate discharge and thermal shock process, they may cause serious safety accidents. At present, mass-produced shells may carry these invisible defects after leaving the factory or assembly, and general metal flaw detection technology is difficult to effectively identify them. Conventional surface morphology scanning or mechanical fatigue testing is also unable to accurately characterize the coupling effect of manganese ion migration and stress corrosion. Therefore, how to accurately identify and quantitatively evaluate such potential defects in the multi-stage process before shell molding and packaging has become a core technical problem that needs to be solved urgently. Summary of the invention
[0005] The main purpose of the present invention is to solve the technical problem that in the existing process of forming the lithium manganese iron phosphate battery shell, the hidden danger of microscopic corrosion caused by the activation of manganese ions cannot be discovered and evaluated in time.
[0006] A first aspect of the present invention provides a shell molding method for a lithium manganese iron phosphate battery, the shell molding method for the lithium manganese iron phosphate battery comprising: In the liquid or semi-solid forming stage of the metal matrix, a part of the metal matrix is obtained as a sample to be tested, and a dual response system is added to the sample to be tested, wherein the dual response system includes an organic coordination group with a manganese ion coordination function and mechanically sensitive particles, and the dual response system is distributed in the interior and surface areas of the sample to be tested to obtain a modified sample to be tested; Applying cyclic heat load and mechanical load to the modified sample to be tested, while introducing a phosphate-containing electrolyte into the modified sample to be tested, obtaining migration and enrichment data of manganese ions in the modified sample to be tested through the dual response system, and obtaining manganese corrosion response data; According to the manganese corrosion response data, the diffusion parameters and stress distortion parameters of the manganese ions are obtained, and the manganese corrosion response data are decoupled and analyzed to obtain stress corrosion data induced by manganese ions; According to the stress corrosion data, the modified sample to be tested is subjected to accelerated aging treatment to obtain spectral response data, local stress data and interface electrochemical data, and the molding process parameters of the remaining metal matrix are adjusted according to the obtained data.
[0007] Optionally, before adding the dual response system to the sample to be tested, the method includes: Performing plasma activation treatment on the sample to be tested to form a nanometer-scale rough structure on the surface of the sample to be tested, thereby obtaining the sample to be tested after surface pretreatment; Inert conductive polymer is introduced into the sample to be tested after the surface pretreatment to form a uniformly distributed conductive layer to obtain the pretreated sample to be tested.
[0008] Optionally, a dual response system is added to the sample to be tested, wherein the dual response system includes an organic coordination group having a manganese ion coordination function and mechanically sensitive particles, and the dual response system is distributed in the interior and surface areas of the sample to be tested to obtain a modified sample to be tested, including: Injecting an organic coordination group containing a multi-thiol group into the internal area of the pretreated sample to be tested, wherein the organic coordination group containing a multi-thiol group forms a stable coordination structure with the manganese ion to obtain an internally modified sample to be tested; Coating nano-metal particles whose surfaces are modified with stress-sensitive groups to the surface area of the internally modified sample to be tested, wherein the nano-metal particles are deformed under the action of mechanical stress to obtain a surface-modified sample to be tested; The surface-modified sample to be tested is subjected to vacuum impregnation treatment, so that the organic coordination groups containing polythiol groups and the nano-metal particles form a coordinated distribution structure, thereby obtaining the modified sample to be tested.
[0009] Optionally, applying cyclic heat load and mechanical load to the modified sample to be tested, and introducing a phosphate-containing electrolyte into the modified sample to be tested, obtaining migration and enrichment data of manganese ions in the modified sample to be tested through the dual response system, and obtaining manganese corrosion response data, including: Passing a phosphate-containing electrolyte into the modified sample to be tested, obtaining an initial coordination signal of the organic coordination group, and obtaining initial coordination data; According to the initial coordination data, applying cyclic thermal load and mechanical load to the modified sample to be tested, obtaining the coordination signal change of the organic coordination group and the deformation signal of the mechanically sensitive particle, and obtaining response change data; According to the response change data, the manganese ion enrichment area in the modified sample to be tested is determined, the stress distribution data of the manganese ion enrichment area is obtained, and the manganese corrosion response data is obtained.
[0010] Optionally, applying cyclic heat load and mechanical load to the modified sample to be tested according to the initial coordination data, obtaining the coordination signal change of the organic coordination group and the deformation signal of the mechanically sensitive particle, and obtaining the response change data, includes: Determine a detection region according to the initial coordination data, perform a thermal cycle treatment on the detection region at a temperature range of 25° C. to 45° C. at a heating rate of 2° C. / min, obtain a change in the coordination signal intensity of the organic coordination group, and obtain thermal response data; A high signal response area is selected according to the thermal response data, and a thermal cycle is performed in a temperature range of 45° C. to 65° C. at a heating rate of 3° C. / min, while a periodic compressive stress of 0.5 MPa to 2 MPa is applied to obtain a coordination signal change curve of the organic coordination group and a stress-strain curve of the mechanically sensitive particle to obtain load response data; According to the load response data, a first ratio of the signal intensity value of each detection point in the coordination signal change curve to the initial coordination data, and a second ratio of the displacement of each detection point in the stress-strain curve to the reference displacement measured at 25°C are calculated, and the overlapping part of the area where the first ratio is greater than 1.5 and the second ratio is greater than 1.002 is calibrated to obtain the response change data.
[0011] Optionally, acquiring the diffusion parameter and stress distortion parameter of the manganese ion according to the manganese corrosion response data, performing decoupling analysis on the manganese corrosion response data, and obtaining the stress corrosion data induced by manganese ions includes: According to the manganese corrosion response data, the coordination signal intensity change rate of the organic coordination group in the temperature range of 25° C. to 65° C. and the deformation response rate of the mechanically sensitive particle in the stress range of 0.5 MPa to 2 MPa are extracted to obtain dual response change data; According to the dual response change data, determining a target region where the ratio of the coordination signal intensity change rate to the deformation response rate is greater than 1.5, and obtaining a diffusion coefficient of manganese ions in the target region; Analyze the change trend of the diffusion coefficient in the temperature range of 45°C to 65°C to obtain the acceleration factor of the diffusion coefficient with increasing temperature; The high-risk area with the acceleration factor greater than 2.0 is determined, the stress concentration coefficient of the high-risk area under the stress of 0.5 MPa to 2 MPa is obtained, and the stress corrosion data induced by manganese ions is obtained.
[0012] Optionally, determining a target region where the ratio of the coordination signal intensity change rate to the deformation response rate is greater than 1.5 according to the dual response change data, and obtaining the diffusion coefficient of manganese ions in the target region includes: Calculating the ratio of the coordination signal intensity change rate to the deformation response rate of each detection point in the dual response change data, and screening out a set of detection points with a ratio greater than 1.5; Performing adjacent point connection analysis on the detection point set, dividing adjacent detection points with a spacing of less than 100 microns into the same target area; The manganese ion concentration gradient data at temperatures of 25° C. and 45° C. are respectively acquired in the target area, and the diffusion coefficient of the manganese ions in the target area is calculated according to the rate of change of the concentration gradient over time.
[0013] Optionally, the modified sample to be tested is subjected to accelerated aging treatment according to the stress corrosion data to obtain spectral response data, local stress data and interface electrochemical data, and the molding process parameters of the remaining metal matrix are adjusted according to the obtained data, including: According to the distribution of high-risk areas induced by manganese ions in the stress corrosion data, the modified sample to be tested is subjected to a 65° C. to 85° C. cycle heating treatment to obtain spectral response data of the organic coordination group; During the cyclic temperature increase treatment, a cyclic stress load of 2 MPa to 5 MPa is applied to the high-risk area to obtain local stress data of the mechanically sensitive particles; Injecting an electrolyte with a pH value of 3 to 4 into the sample to be tested, applying a potential scan from -0.5 V to 1.0 V to the high-risk area, and acquiring interface electrochemical data; Determine the accelerated corrosion rate of the high-risk area according to the spectral response data, local stress data and interface electrochemical data, and establish a corresponding relationship between manganese corrosion risk and molding process parameters; According to the corresponding relationship, the forming temperature, stress distribution and surface treatment process parameters of the remaining metal matrix are adjusted to achieve process control of manganese corrosion risk.
[0014] A second aspect of the present invention provides a lithium manganese iron phosphate battery, the lithium manganese iron phosphate battery comprising a shell, and the shell is prepared by the shell molding method of the lithium manganese iron phosphate battery described in the above embodiment.
[0015] The technical solution provided in the embodiment of the present application is to extract part of the material as the sample to be tested when the metal matrix is still in a liquid state or semi-solidified, and add a combination structure containing an organic coordination group and mechanically sensitive particles thereto so that it is evenly distributed on the surface and inside of the sample. The original intention of doing so is that a probe that can respond to the coordination behavior of manganese ions and stress changes has been buried at the key node before the material is fully finalized. Subsequently, a cyclic heat load and a mechanical load are applied to the modified sample, and a phosphate-containing electrolyte is introduced at the same time. Since the organic coordination group will produce a characteristic coordination signal with the migrated or enriched manganese ions, and the mechanically sensitive particles will respond to the local stress distortion, these two types of signals together constitute a set of monitoring systems that can reflect the process of "diffusion and stress state evolution of manganese in the metal matrix" in real time. On this basis, by decoupling the manganese corrosion response data, the degree and distribution of manganese ion-induced stress corrosion can be analyzed, providing direction for subsequent accelerated aging treatment. Finally, the corrosion risk is comprehensively evaluated through various data such as spectral response, local stress, and interface electrochemistry, and targeted adjustments are made to the forming process of the remaining metal matrix (such as parameters such as temperature gradient, surface treatment, or stress distribution).
[0016] This idea of detecting and grading manganese-induced corrosion in the early stage of self-forming has greatly improved the ability to capture microscopic hidden defects. Compared with only doing finished product testing in the later stage, the potential activation tendency of manganese ions and local stress concentration areas can be sensed before the macroscopic finalization of the material. Once microcracks or local corrosion begin to initiate, the above-mentioned dual-response system will show corresponding disturbances in the chemical coordination signal and mechanical deformation signal, and can quantify the output of key parameters such as the diffusion coefficient of manganese ions and the degree of stress concentration. Accelerated aging further amplifies these early signs, making the hidden dangers that may only erupt in high-rate discharge or thermal shock in the later stage appear in advance, and the process control link can modify the temperature curve, pressure application method, surface passivation treatment or nanostructure modification during forming, thereby reducing the probability of large-scale diffusion or local concentration of stress corrosion at the source. Through this series of detection and control methods throughout the entire forming process, it is possible to effectively solve the problem of accurately identifying and quantitatively evaluating microscopic corrosion hazards in the early stage, and realize the rapid early warning and prevention and control of corrosion risks caused by manganese activation characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0018] Figure 1 Schematic diagram of an embodiment of a method for forming a shell of a lithium manganese iron phosphate battery in an embodiment of the present invention.
[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0022] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, "and / or" in the full text includes three solutions. Taking A and / or B as an example, it includes technical solution A, technical solution B, and technical solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, which must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0023] An embodiment of the present application provides a shell molding method for a lithium manganese iron phosphate battery. Figure 1 A flow chart of a shell forming method for a lithium manganese iron phosphate battery provided in an embodiment of the present application. In this embodiment, the method includes: See also Figure 1 , in the liquid or semi-solid forming stage of the metal matrix, a part of the metal matrix is obtained as a sample to be tested, and a dual response system is added to the sample to be tested, wherein the dual response system includes an organic coordination group with a manganese ion coordination function and mechanically sensitive particles, and the dual response system is distributed in the interior and surface areas of the sample to be tested to obtain a modified sample to be tested; In one embodiment of the present invention, before adding the dual response system to the sample to be tested, the method comprises: Performing plasma activation treatment on the sample to be tested to form a nanometer-scale rough structure on the surface of the sample to be tested, thereby obtaining the sample to be tested after surface pretreatment; Inert conductive polymer is introduced into the sample to be tested after the surface pretreatment to form a uniformly distributed conductive layer to obtain the pretreated sample to be tested.
[0024] The following is a detailed description of the steps involved in the above embodiment: When plasma activation treatment is performed on the sample to be tested, the sample to be tested needs to be placed in a vacuum environment, and by introducing inert gases such as argon or nitrogen and maintaining stable radio frequency or direct current power, ions form a high-speed bombardment effect on the surface of the sample to be tested. Commonly used instruments include radio frequency plasma systems or direct current glow discharge devices, and the specific values of gas flow and plasma power are controlled according to the material tolerance and nanostructure requirements. Ion bombardment will remove the relatively flat oxide layer or other attachments on the surface of the sample to be tested, and produce uneven textures on a microscopic scale, so that the surface is distributed with nano-level protrusions or holes. By adjusting the treatment time and gas type, different degrees of roughness can be obtained, so that the subsequently introduced substances are easier to disperse in the nanopores. The result of this process is the formation of a three-dimensional structure in the surface area, which is conducive to the subsequent introduction of substances and the metal matrix Close combination, increase the overall stability.
[0025] After completing the above-mentioned surface activation, the inert conductive polymer needs to be evenly coated or infiltrated into the pretreated surface area. Optional inert conductive polymers include polyaniline, polypyrrole or poly (3,4-ethylenedioxythiophene), which have good conductivity and strong chemical inertness. Such polymers are generally introduced by solution coating or electrochemical deposition. A spin coater or electrochemical workstation can be used on the instrument to ensure continuous distribution without obvious faults in the surface microstructure. If the dispersion needs to be further improved, appropriate temperature control or slight vacuum assistance can be used to allow the polymer to fully diffuse in the nanopores. Through this process, a uniform and continuous conductive polymer network is finally formed on the rough surface. This design not only improves the overall conductivity, but also achieves more uniform stress transfer and electrochemical environment distribution when it is subsequently exposed to various electrochemical or mechanical loads.
[0026] In one embodiment of the present invention, a dual response system is added to the sample to be tested, wherein the dual response system includes an organic coordination group having a manganese ion coordination function and a mechanically sensitive particle, and the dual response system is distributed in the interior and surface areas of the sample to be tested to obtain a modified sample to be tested, including: Injecting an organic coordination group containing a multi-thiol group into the internal area of the pretreated sample to be tested, wherein the organic coordination group containing a multi-thiol group forms a stable coordination structure with the manganese ion to obtain an internally modified sample to be tested; Coating nano-metal particles whose surfaces are modified with stress-sensitive groups to the surface area of the internally modified sample to be tested, wherein the nano-metal particles are deformed under the action of mechanical stress to obtain a surface-modified sample to be tested; The surface-modified sample to be tested is subjected to vacuum impregnation treatment, so that the organic coordination groups containing polythiol groups and the nano-metal particles form a coordinated distribution structure, thereby obtaining the modified sample to be tested.
[0027] The following is a detailed description of the steps involved in the above embodiment: In the first step, the pretreated sample to be tested is placed in a special impregnation or injection device, and an organic solution or precursor containing multiple thiol functional groups is introduced to allow the solution to gradually penetrate into the internal area of the sample to be tested. In order to ensure that the solution fully penetrates the pores and microcracks, low-pressure impregnation or constant flow rate injection can be combined, and a constant time can be maintained under a certain temperature environment to allow the thiol groups to be firmly dispersed inside the material. Organic compounds with multi-thiol structures form stable coordination bonds with metal ions, and will exhibit characteristic coordination behavior when they subsequently come into contact with manganese ions. Therefore, this approach can be used to enhance the tracking of manganese ion enrichment or diffusion processes. After this step is completed, the internally modified sample obtained will provide a more obvious coordination signal when it subsequently comes into contact with exogenous manganese ions.
[0028] In the second step, nanoscale metal particles are evenly dispersed on the surface area of the internal modified sample by coating or spraying, and stress sensitive groups are attached to the surface of these metal particles. Spin coaters or inkjet deposition instruments can be used to control the coating thickness and uniformity, so that the stress sensitive groups are stably combined with the metal particles and form a continuous or semi-continuous distribution on the surface. The type of metal particles can be selected according to the mechanical response requirements, such as using silver or gold-based nanostructures that are more sensitive to local stress changes. The surface modified sample formed in this step will undergo slight deformation in the particle layer when subjected to mechanical load, and generate recordable or quantifiable signals through stress sensitive groups, thereby reflecting local stress concentration or deformation.
[0029] In the third step, the surface modified sample is further placed in a vacuum impregnation device, maintaining the preset vacuum and temperature conditions, so that the polythiol organic coordination groups and the nano-metal particles can penetrate and coordinate with each other at the interface. This process can be assisted by step-by-step vacuum adjustment or low-viscosity solvent treatment, so that the modified components inside and on the surface gradually contact and form a tight bond in the nanopores or microstructures. After this operation is completed, the modified sample has the dual signal response capability to the electrochemical environment and mechanical stress at the overall level, and has the synergistic coupling effect between the internal coordination groups and the surface particles. After this step, the modified sample can more stably capture and feedback signs of manganese ion migration and stress corrosion in subsequent environments.
[0030] Please continue reading Figure 1 , applying cyclic heat load and mechanical load to the modified sample to be tested, and introducing a phosphate-containing electrolyte into the modified sample to be tested, obtaining migration and enrichment data of manganese ions in the modified sample to be tested through the dual response system, and obtaining manganese corrosion response data; In one embodiment of the present invention, the step of applying a cyclic heat load and a mechanical load to the modified sample to be tested, and simultaneously introducing a phosphate-containing electrolyte into the modified sample to be tested, and obtaining migration and enrichment data of manganese ions in the modified sample to be tested through the dual response system to obtain manganese corrosion response data includes: Passing a phosphate-containing electrolyte into the modified sample to be tested, obtaining an initial coordination signal of the organic coordination group, and obtaining initial coordination data; According to the initial coordination data, applying cyclic thermal load and mechanical load to the modified sample to be tested, obtaining the coordination signal change of the organic coordination group and the deformation signal of the mechanically sensitive particle, and obtaining response change data; According to the response change data, the manganese ion enrichment area in the modified sample to be tested is determined, the stress distribution data of the manganese ion enrichment area is obtained, and the manganese corrosion response data is obtained.
[0031] The following is a detailed description of the steps involved in the above embodiment: In the first step, the modified sample to be tested is placed in a sealed or open container, and a phosphate-containing electrolyte solution or aerosol is introduced to allow the electrolyte to fully contact the organic coordination group. The injection method can use a constant pressure or flow injection device, combined with a certain period of immersion or flow process to ensure that the organic coordination group and the phosphate environment reach a stable binding state. Under this condition, the starting signal corresponding to the organic coordination group is recorded by fluorescence, absorption spectroscopy or electrochemical workstation to obtain the initial coordination data for subsequent comparison and analysis. This step presents the basic degree of binding between the internal modified structure and the external electrolyte by measuring the coordination state without external load.
[0032] In the second step, based on the initial coordination data obtained above, cyclic thermal load and mechanical load are applied to the modified sample to be tested. The cyclic thermal load can be set up by a high and low temperature alternating test chamber to change the temperature from a lower temperature to a higher temperature, and maintain a predetermined time in each temperature range; the mechanical load applies a pressure or tensile force of a specific size and frequency through a loading platform or a material fatigue testing machine. In this process, the drift of the organic coordination group signal is monitored by spectroscopy or electrochemical means, and the deformation data of the mechanically sensitive particles is collected by strain gauges or nanoparticle sensors. The changes in the coordination signal and the deformation signal are recorded and correlated to obtain the response change data. This step helps to observe the coupling effect of the internal coordination system and the surface mechanically sensitive structure under the superposition of thermal stress and mechanical stress.
[0033] In the third step, based on the aforementioned response change data, the spatial distribution of the coordination signal and the deformation signal and the trend of change with load can be analyzed to determine the location of the region where manganese ions are enriched in the modified sample to be tested. To further quantify the mechanical state of these areas, the stress distribution test system (such as micro-area Raman stress measurement or high-resolution strain sensor) can be used to scan the specified position point by point or area to obtain the stress distribution data corresponding to the manganese ion enrichment, and the two can be combined to generate manganese corrosion response data. Through this process, the relationship between manganese ion diffusion enrichment and local stress concentration can be understood at the macro and micro levels, providing a scientific basis for subsequent molding process regulation or failure prevention measures.
[0034] In one embodiment of the present invention, the modified sample to be tested is subjected to cyclic thermal load and mechanical load according to the initial coordination data, and the coordination signal change of the organic coordination group and the deformation signal of the mechanically sensitive particle are obtained to obtain the response change data, including: Determine a detection region according to the initial coordination data, perform a thermal cycle treatment on the detection region at a temperature range of 25° C. to 45° C. at a heating rate of 2° C. / min, obtain a change in the coordination signal intensity of the organic coordination group, and obtain thermal response data; A high signal response area is selected according to the thermal response data, and a thermal cycle is performed in a temperature range of 45° C. to 65° C. at a heating rate of 3° C. / min, while a periodic compressive stress of 0.5 MPa to 2 MPa is applied to obtain a coordination signal change curve of the organic coordination group and a stress-strain curve of the mechanically sensitive particle to obtain load response data; According to the load response data, a first ratio of the signal intensity value of each detection point in the coordination signal change curve to the initial coordination data, and a second ratio of the displacement of each detection point in the stress-strain curve to the reference displacement measured at 25°C are calculated, and the overlapping part of the area where the first ratio is greater than 1.5 and the second ratio is greater than 1.002 is calibrated to obtain the response change data.
[0035] The following is a detailed description of the steps involved in the above embodiment: In the first step, based on the previous coordination data, select the detection area with obvious coordination signal difference under normal temperature conditions (about 25°C), and use a controllable temperature device or a high and low temperature test chamber to increase the temperature from 25°C to 45°C, and set the heating rate to 2°C / min. The consideration of this range and speed setting is to conduct a preliminary exploration of the thermosensitive properties of the organic coordination groups in the material, and 25°C to 45°C usually covers the transition stage of the sample from room temperature to slightly higher than the normal operating environment. During this heating process, the coordination signal may tend to gradually increase or decrease with the increase in temperature. By collecting the signal intensity changes by spectroscopy or electrochemistry, the preliminary thermal response law presented in the low to medium temperature range can be identified. The thermal response data obtained at this stage provides a reference threshold for subsequent tests in a larger temperature range, so as to more accurately define the high signal response area.
[0036] In the second step, the detection points showing obvious changes in coordination signals or high curve fluctuations in the above thermal response data are selected, and the temperature is continued to rise from 45°C to 65°C using the same or similar controllable temperature device, and the heating rate is adjusted to 3°C / min. This temperature range and heating rate are higher and faster than the previous stage, aiming to simulate a more stringent working environment while amplifying the thermosensitive response of the organic coordination group. During the heating process, a cyclical compressive stress of 0.5MPa to 2MPa is applied through a loading platform or a material mechanical testing machine. The cyclical stress usually simulates the mechanical shock or fatigue load that the material may encounter in the use scenario. Use strain gauges or other mechanical sensing equipment to record the stress-strain curve of the particles, and monitor the intensity changes of the coordination signal curve in parallel to obtain load response data. This is done to identify potential areas in the material that are more prone to coupled stress corrosion under the combined action of temperature and stress, and to determine the signal performance of the organic coordination group at different stress levels.
[0037] In the third step, based on the aforementioned load response data, the signal intensity ratio of each detection point in the coordination signal curve of the organic ligand group relative to the initial coordination data, and the ratio of each detection point in the stress-strain curve of the mechanically sensitive particle relative to the displacement under the 25°C reference condition are calculated respectively. Through comparative analysis, the overlapping parts of the regions where the signal intensity ratio exceeds 1.5 times and the displacement ratio exceeds 1.002 times are determined. These overlapping areas indicate that there are obvious coordination signal fluctuations and mechanical responses beyond the normal range, which means that under the combined action of temperature increase and periodic compressive stress, these areas show abnormal activity. The response change data obtained by this quantitative ratio analysis method can accurately identify potential corrosion and stress concentration risk areas in the material, and provide clear target areas for subsequent regulation or accelerated aging treatment.
[0038] Please continue reading Figure 1, according to the manganese corrosion response data, the diffusion parameters and stress distortion parameters of the manganese ions are obtained, and the manganese corrosion response data are decoupled and analyzed to obtain the stress corrosion data induced by manganese ions; In one embodiment of the present invention, the diffusion parameters and stress distortion parameters of the manganese ions are obtained according to the manganese corrosion response data, and the manganese corrosion response data are decoupled and analyzed to obtain the stress corrosion data induced by manganese ions, including: According to the manganese corrosion response data, the coordination signal intensity change rate of the organic coordination group in the temperature range of 25° C. to 65° C. and the deformation response rate of the mechanically sensitive particle in the stress range of 0.5 MPa to 2 MPa are extracted to obtain dual response change data; According to the dual response change data, determining a target region where the ratio of the coordination signal intensity change rate to the deformation response rate is greater than 1.5, and obtaining a diffusion coefficient of manganese ions in the target region; Analyze the change trend of the diffusion coefficient in the temperature range of 45°C to 65°C to obtain the acceleration factor of the diffusion coefficient with increasing temperature; The high-risk area with the acceleration factor greater than 2.0 is determined, the stress concentration coefficient of the high-risk area under the stress of 0.5 MPa to 2 MPa is obtained, and the stress corrosion data induced by manganese ions is obtained.
[0039] The following is a detailed description of the steps involved in the above embodiment: In the first step, based on the manganese corrosion response data obtained from previous detection and analysis, the coordination signals of organic ligand groups collected under temperature conditions of 25°C to 65°C were selected, and combined with the deformation records of mechanically sensitive particles in the stress range of 0.5MPa to 2MPa, the slope of the coordination signal intensity changing with temperature and the slope of the particle deformation degree changing with stress were calculated respectively. The temperature range involves room temperature to moderate heating range, and the temperature can be gradually increased and the spectral or electrochemical signals can be recorded with the help of a high and low temperature cycle box or a controlled environment chamber; the stress range covers moderate mechanical loads, and the material mechanical testing machine or strain gauge acquisition device can be used to adjust the load and measure in real time. By separately deriving or differentially processing the coordination signal and deformation data, the change rate of the coordination signal intensity and the deformation response rate can be intuitively obtained. At this stage, the synchronous evolution of the chemical coordination process and the mechanical deformation process in the material is confirmed.
[0040] In the second step, based on the dual response change data obtained in the first paragraph, by comparing the ratio of the coordination signal intensity change rate to the deformation response rate, the area above 1.5 is selected as the target area, and then the manganese ion diffusion process in the target area is calculated. If the diffusion coefficient needs to be further analyzed, the well-known Fick diffusion equation or other electrochemical analysis models commonly used in the field of materials science can be combined to fit or interpolate the evolution trend of the concentration distribution of manganese ions in the target area over time or space. This type of diffusion model is generally widely used in the fields of materials science and corrosion analysis to describe the transport behavior of ions in solid or liquid media. Based on this method, the manganese ion diffusion coefficient in the target area can be obtained, laying a numerical foundation for evaluating potential corrosion sensitivity.
[0041] In the third step, the diffusion coefficient determined in the previous step is used to evaluate the acceleration effect of the diffusion rate with increasing temperature in the temperature range of 45°C to 65°C. The Arrhenius relationship or other common temperature-dependent models can be combined to analyze the trend of the diffusion rate to extract the acceleration factor. Such models are generally regarded as mature theoretical means to characterize the doubling of diffusion or reaction rates in different temperature ranges, which helps to quickly quantify the corrosion risks faced by materials under higher temperature conditions. The consideration of selecting the upper temperature limit of 65°C is to cover the temperature upper limit of common application scenarios and to reveal the potential for high temperature accelerated corrosion within a safe range.
[0042] In the fourth step, the area with an acceleration factor greater than 2.0 is screened and identified as a high-risk area. Then, a stress of 0.5MPa to 2MPa is applied within this range and the stress concentration coefficient of the mechanically sensitive particles is measured, and finally the stress corrosion data induced by manganese ions is obtained. The acceleration factor threshold can be understood as a dividing point for the diffusion enhancement phenomenon. If the value increases significantly, it means that the risk of manganese migration inside the material is higher under this temperature condition. At this time, by comparing the changes in the stress concentration coefficient under different load levels, the corresponding relationship between corrosion intensity and mechanical distortion can be established. This step is completed using strain gauges or high-resolution stress distribution test equipment. The recorded stress concentration information is combined with the previous diffusion analysis to clearly identify the distribution of coupled corrosion hazards in the material due to manganese activation behavior.
[0043] In one embodiment of the present invention, determining a target region where the ratio of the coordination signal intensity change rate to the deformation response rate is greater than 1.5 based on the dual response change data, and obtaining the diffusion coefficient of manganese ions in the target region includes: Calculating the ratio of the coordination signal intensity change rate to the deformation response rate of each detection point in the dual response change data, and screening out a set of detection points with a ratio greater than 1.5; Performing adjacent point connection analysis on the detection point set, dividing adjacent detection points with a spacing of less than 100 microns into the same target area; The manganese ion concentration gradient data at temperatures of 25° C. and 45° C. are respectively acquired in the target area, and the diffusion coefficient of the manganese ions in the target area is calculated according to the rate of change of the concentration gradient over time.
[0044] The following is a detailed description of the steps involved in the above embodiment: In the first step, it is necessary to extract the coordination signal intensity change rate and the deformation response rate point by point in the dual response change data, and divide the two values to obtain the corresponding ratio. This calculation link can be processed in batches with the help of numerical analysis software or script writing, and each detection point is assigned a ratio. During operation, the coordination signal and deformation data are first baseline calibrated to ensure the comparability between different measurement conditions. For detection points with a ratio exceeding 1.5, they can be marked in the data table or classified separately to finally form a set of detection points. A ratio that is too high often means that the response of the organic coordination group at this position is significantly higher than the mechanical deformation level, suggesting more obvious chemical activity or corrosion sensitivity.
[0045] In the second step, it is necessary to perform adjacent point connection analysis based on the spatial coordinate information of the detection point set. This process can be done by clustering the detection points or calculating the nearest distance through two-dimensional or three-dimensional data visualization tools, and treating any two points with a distance less than 100 microns as a continuous distribution, and then assigning these adjacent points to the same target area. The above approach is conducive to aggregating scattered high-value points into coherent areas, making subsequent positioning and processing more targeted. For application scenarios that may require extremely high resolution, correlation analysis can be combined with micro-area microscopy technology to accurately calibrate the detection point position, thereby further improving data accuracy.
[0046] In the third step, for the identified target area, the manganese ion concentration gradient is collected at 25°C and 45°C respectively. The concentration gradient can be measured by micro-area electrochemical probe, X-ray energy spectrum or other common component distribution analysis methods. By performing differential or slope calculations on the concentration distribution curves at different time points at the same temperature, the rate of change of the concentration gradient over time can be obtained, and the diffusion coefficient of manganese ions in the target area can be calculated in combination with materials science knowledge or recognized diffusion models. 25°C and 45°C were selected to compare the difference in the diffusion capacity of manganese in this area under normal temperature and moderate temperature rise, so that the subsequent assessment of corrosion risks and process adjustments will be more valuable for reference.
[0047] Please continue reading Figure 1According to the stress corrosion data, the modified sample to be tested is subjected to accelerated aging treatment to obtain spectral response data, local stress data and interface electrochemical data, and the molding process parameters of the remaining metal matrix are adjusted according to the acquired data.
[0048] In one embodiment of the present invention, the modified sample to be tested is subjected to accelerated aging treatment according to the stress corrosion data, spectral response data, local stress data and interface electrochemical data are obtained, and the molding process parameters of the remaining metal matrix are adjusted according to the obtained data, including: According to the distribution of high-risk areas induced by manganese ions in the stress corrosion data, the modified sample to be tested is subjected to a 65° C. to 85° C. cycle heating treatment to obtain spectral response data of the organic coordination group; During the cyclic temperature increase treatment, a cyclic stress load of 2 MPa to 5 MPa is applied to the high-risk area to obtain local stress data of the mechanically sensitive particles; Injecting an electrolyte with a pH value of 3 to 4 into the sample to be tested, applying a potential scan from -0.5 V to 1.0 V to the high-risk area, and acquiring interface electrochemical data; Determine the accelerated corrosion rate of the high-risk area according to the spectral response data, local stress data and interface electrochemical data, and establish a corresponding relationship between manganese corrosion risk and molding process parameters; According to the corresponding relationship, the forming temperature, stress distribution and surface treatment process parameters of the remaining metal matrix are adjusted to achieve process control of manganese corrosion risk.
[0049] The following is a detailed description of the steps involved in the above embodiment: In the first step, it is necessary to first identify the specific location of the high-risk area based on the stress corrosion data obtained in the early stage, and then place the modified sample to be tested in a programmable thermal cycler or a high and low temperature test chamber, so that its temperature fluctuates between 65°C and 85°C, and collect the spectral signal of the organic coordination group during the specified period. Spectral analysis can be completed through absorption spectroscopy or fluorescence spectroscopy devices, and the response amplitude of the coordination group can be observed in real time according to the characteristic peak position of different coordination groups. The reason for the cyclic heating treatment in the range of 65°C to 85°C is to amplify the possible corrosion phenomenon in a higher temperature range, to facilitate the identification of the sensitivity of high-risk parts to the thermal environment, and to obtain coordination behavior data under high temperature conditions.
[0050] In the second step, while performing cyclic heating, it is necessary to apply a stress of 2MPa to 5MPa in the high-risk area, and set the loading mode to pulse or intermittent cycle. The mechanical loading equipment can be a material mechanical testing machine or a multi-channel mechanical load platform, and the load and unloading are applied and unloaded at a fixed time through a pre-programmed control program. Mechanically sensitive particles will undergo significant deformation under stress, and local stress data can be collected with the help of strain gauges or other micro-area sensors. The range of 2MPa to 5MPa is selected considering that a certain degree of mechanical stress can often aggravate the expansion of material defects, thereby amplifying the corrosion response in a high temperature environment, thereby obtaining more differentiated data information.
[0051] In the third step, after completing the aforementioned thermal and mechanical coupling operations, an electrolyte with a pH of 3 to 4 is introduced into the sample to be tested, and a potential scan from -0.5V to 1.0V is performed on the high-risk area. The pH range of 3 to 4 can make the environment present a strong acidic characteristic, thereby further accelerating the corrosion process, so as to evaluate the actual performance of the high-risk area under a strong corrosion environment. The potential scan can be performed by an electrochemical workstation, and a forward or reverse scan is performed in the above potential interval during operation, and the current response curve is recorded. The interfacial electrochemical data obtained in this way can reflect the corrosion kinetics characteristics of the modified layer or metal matrix in an acidic environment.
[0052] In the fourth step, the above spectral response data, local stress data and interface electrochemical data are comprehensively compared and summarized into the same analysis platform or multi-dimensionally correlated with the help of data processing software to calculate the corrosion rate of high-risk areas under the interactive conditions of temperature rise, stress and acidic environment. The spectral response can reveal the change of the chemical state of the coordination group, the mechanical data can reflect the degree of local deformation, and the electrochemical results can show the redox or ion migration behavior. Through longitudinal or transverse numerical comparison, the manganese corrosion risk can be quickly evaluated under different load and temperature conditions, and the corresponding relationship between the manganese corrosion risk and the molding process parameters can be formed, so as to find the link that is most likely to trigger corrosion under a specific parameter combination.
[0053] In the fifth step, according to the above correspondence, the molding process conditions of the remaining metal matrix are adjusted. The temperature curve during molding can be fine-tuned, a more appropriate pressure distribution strategy can be selected, or the material formulation and treatment sequence during the surface treatment process can be changed to reduce the corrosion inducement in the high-risk area at the source. The adjustment strategy can be executed when the temperature control equipment is combined with the mechanical loading platform, and the cleaning or activation parameters can be changed before surface treatment to reduce the impact of manganese ion diffusion and stress concentration on material safety. By appropriately correcting the molding process parameters, the effect of reducing potential corrosion failures and improving overall reliability can be achieved.
[0054] The present invention also proposes a lithium iron phosphate battery, which includes a shell. The preparation method of the shell adopts the shell molding method of the lithium iron phosphate battery in any of the above embodiments. Therefore, the lithium iron phosphate battery has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here one by one.
[0055] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A shell forming method for a lithium manganese iron phosphate battery, characterized in that: include: In the liquid or semi-solid forming stage of the metal matrix, a part of the metal matrix is obtained as a sample to be tested, and a dual response system is added to the sample to be tested, wherein the dual response system includes an organic coordination group with a manganese ion coordination function and mechanically sensitive particles, and the dual response system is distributed in the interior and surface areas of the sample to be tested to obtain a modified sample to be tested; Applying cyclic heat load and mechanical load to the modified sample to be tested, while introducing a phosphate-containing electrolyte into the modified sample to be tested, obtaining migration and enrichment data of manganese ions in the modified sample to be tested through the dual response system, and obtaining manganese corrosion response data; According to the manganese corrosion response data, the diffusion parameters and stress distortion parameters of the manganese ions are obtained, and the manganese corrosion response data are decoupled and analyzed to obtain stress corrosion data induced by manganese ions; According to the stress corrosion data, the modified sample to be tested is subjected to accelerated aging treatment to obtain spectral response data, local stress data and interface electrochemical data, and the molding process parameters of the remaining metal matrix are adjusted according to the obtained data.
2. The shell forming method of the lithium manganese iron phosphate battery according to claim 1, characterized in that: Before adding the dual response system to the sample to be tested, the method comprises: Performing plasma activation treatment on the sample to be tested to form a nanometer-scale rough structure on the surface of the sample to be tested, thereby obtaining the sample to be tested after surface pretreatment; Inert conductive polymer is introduced into the sample to be tested after the surface pretreatment to form a uniformly distributed conductive layer to obtain the pretreated sample to be tested.
3. The shell forming method of the lithium manganese iron phosphate battery according to claim 2, characterized in that: The dual response system is added to the sample to be tested, wherein the dual response system includes an organic coordination group having a manganese ion coordination function and mechanically sensitive particles, and the dual response system is distributed in the interior and surface areas of the sample to be tested to obtain a modified sample to be tested, including: Injecting an organic coordination group containing a multi-thiol group into the internal area of the pretreated sample to be tested, wherein the organic coordination group containing a multi-thiol group forms a stable coordination structure with the manganese ion to obtain an internally modified sample to be tested; Coating nano-metal particles whose surfaces are modified with stress-sensitive groups to the surface area of the internally modified sample to be tested, wherein the nano-metal particles are deformed under the action of mechanical stress to obtain a surface-modified sample to be tested; The surface-modified sample to be tested is subjected to vacuum impregnation treatment, so that the organic coordination groups containing polythiol groups and the nano-metal particles form a coordinated distribution structure, thereby obtaining the modified sample to be tested.
4. The shell forming method of the lithium manganese iron phosphate battery according to claim 1, characterized in that: The step of applying cyclic heat load and mechanical load to the modified sample to be tested, and introducing a phosphate-containing electrolyte into the modified sample to be tested, and obtaining migration and enrichment data of manganese ions in the modified sample to be tested through the dual response system to obtain manganese corrosion response data, includes: Passing a phosphate-containing electrolyte into the modified sample to be tested, obtaining an initial coordination signal of the organic coordination group, and obtaining initial coordination data; According to the initial coordination data, applying cyclic thermal load and mechanical load to the modified sample to be tested, obtaining the coordination signal change of the organic coordination group and the deformation signal of the mechanically sensitive particle, and obtaining response change data; According to the response change data, the manganese ion-enriched area in the modified sample to be tested is determined, the stress distribution data of the manganese ion-enriched area is obtained, and the manganese corrosion response data is obtained.
5. The shell forming method of the lithium manganese iron phosphate battery according to claim 4, characterized in that: According to the initial coordination data, applying cyclic heat load and mechanical load to the modified sample to be tested, obtaining the coordination signal change of the organic coordination group and the deformation signal of the mechanically sensitive particle, and obtaining response change data, including: Determine a detection region according to the initial coordination data, perform a thermal cycle treatment on the detection region at a temperature range of 25° C. to 45° C. at a heating rate of 2° C. / min, obtain a change in the coordination signal intensity of the organic coordination group, and obtain thermal response data; A high signal response area is selected according to the thermal response data, and a thermal cycle is performed in a temperature range of 45° C. to 65° C. at a heating rate of 3° C. / min, while a periodic compressive stress of 0.5 MPa to 2 MPa is applied to obtain a coordination signal change curve of the organic coordination group and a stress-strain curve of the mechanically sensitive particle to obtain load response data; According to the load response data, a first ratio of the signal intensity value of each detection point in the coordination signal change curve to the initial coordination data, and a second ratio of the displacement of each detection point in the stress-strain curve to the reference displacement measured at 25°C are calculated, and the overlapping part of the area where the first ratio is greater than 1.5 and the second ratio is greater than 1.002 is calibrated to obtain the response change data.
6. The method for forming a shell of a lithium manganese iron phosphate battery according to claim 1, characterized in that: The step of obtaining the diffusion parameters and stress distortion parameters of the manganese ions according to the manganese corrosion response data, performing decoupling analysis on the manganese corrosion response data, and obtaining the stress corrosion data induced by manganese ions includes: According to the manganese corrosion response data, the coordination signal intensity change rate of the organic coordination group in the temperature range of 25° C. to 65° C. and the deformation response rate of the mechanically sensitive particle in the stress range of 0.5 MPa to 2 MPa are extracted to obtain dual response change data; Determine, according to the dual response change data, a target region where the ratio of the coordination signal intensity change rate to the deformation response rate is greater than 1.5, and obtain the diffusion coefficient of manganese ions in the target region; Analyze the change trend of the diffusion coefficient in the temperature range of 45°C to 65°C to obtain the acceleration factor of the diffusion coefficient with increasing temperature; The high-risk area with the acceleration factor greater than 2.0 is determined, the stress concentration coefficient of the high-risk area under the stress of 0.5 MPa to 2 MPa is obtained, and the stress corrosion data induced by manganese ions is obtained.
7. The method for forming a shell of a lithium manganese iron phosphate battery according to claim 6, characterized in that: The step of determining a target region where the ratio of the coordination signal intensity change rate to the deformation response rate is greater than 1.5 based on the dual response change data, and obtaining the diffusion coefficient of manganese ions in the target region includes: Calculating the ratio of the coordination signal intensity change rate to the deformation response rate of each detection point in the dual response change data, and screening out a set of detection points with a ratio greater than 1.5; Performing adjacent point connection analysis on the detection point set, dividing adjacent detection points with a spacing of less than 100 microns into the same target area; The manganese ion concentration gradient data at temperatures of 25° C. and 45° C. are respectively acquired in the target area, and the diffusion coefficient of the manganese ions in the target area is calculated according to the rate of change of the concentration gradient over time.
8. The method for forming a shell of a lithium manganese iron phosphate battery according to claim 1, characterized in that: According to the stress corrosion data, the modified sample to be tested is subjected to accelerated aging treatment to obtain spectral response data, local stress data and interface electrochemical data, and the molding process parameters of the remaining metal matrix are adjusted according to the obtained data, including: According to the distribution of high-risk areas induced by manganese ions in the stress corrosion data, the modified sample to be tested is subjected to a 65° C. to 85° C. cycle heating treatment to obtain spectral response data of the organic coordination group; During the cyclic temperature increase treatment, a cyclic stress load of 2 MPa to 5 MPa is applied to the high-risk area to obtain local stress data of the mechanically sensitive particles; Injecting an electrolyte with a pH value of 3 to 4 into the sample to be tested, applying a potential scan from -0.5 V to 1.0 V to the high-risk area, and acquiring interface electrochemical data; Determine the accelerated corrosion rate of the high-risk area according to the spectral response data, local stress data and interface electrochemical data, and establish a corresponding relationship between manganese corrosion risk and molding process parameters; According to the corresponding relationship, the forming temperature, stress distribution and surface treatment process parameters of the remaining metal matrix are adjusted to achieve process control of manganese corrosion risk.
9. A lithium manganese iron phosphate battery, characterized in that: The lithium manganese iron phosphate battery includes a shell, and the shell is prepared by the shell molding method of the lithium manganese iron phosphate battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Electrochemical-thermal-mechanical coupling model of lithium ion battery and modeling method
CN110457742A
Isolating membrane, lithium ion battery, battery module, battery pack and electric device
CN116601817A
Two-dimensional electrochemical-thermal-mechanical coupling model of full-tab cylindrical lithium ion battery and modeling method of two-dimensional electrochemical-thermal-mechanical coupling model
CN116956620A
New metal material intergranular corrosion test method
CN118425014A
Method of pipeline corrosion monitoring
RU2653775C1